The TESOL Encyclopedia of English Language Teaching 2018
DOI: 10.1002/9781118784235.eelt0670
|View full text |Cite
|
Sign up to set email alerts
|

First Language and Assessing English as an International Language

Abstract: The globalization of English has resulted in the constant contact of this language with indigenous languages in the periphery and hence unprecedented variation in the norms of the English‐speaking world. Notwithstanding this variation, the dominant paradigm of English language assessment is still based strongly on an invariant, monolithic view of the language. As a result, a call for a “paradigm shift” to address the above situation is evident in the current English language teaching scholarship. In this new p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The students in Nguyen (2008) also complained that they were misled by the beautiful pictures and colorful effects. Nguyen also noted that in some cases, PPT slides could be counter-effective and distracting as students kept discussing the slide pictures and did not pay adequate attention to what they were required to do by teachers.…”
Section: Students' Positive Attitudes Towards Ppt Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The students in Nguyen (2008) also complained that they were misled by the beautiful pictures and colorful effects. Nguyen also noted that in some cases, PPT slides could be counter-effective and distracting as students kept discussing the slide pictures and did not pay adequate attention to what they were required to do by teachers.…”
Section: Students' Positive Attitudes Towards Ppt Applicationsmentioning
confidence: 99%
“…In the study Schcolnik and Kol (1999) reported on two uses of PPT that they had applied in the language classroom: one as a presentation tool, and the other as a novel writing tool and they found that oral presentation through PPT improved meaningful interaction. According to one Vietnamese study, PPT may enhance visual, audio, and psychological interactions and negotiation of meaning (Nguyen, 2008). Several research studies in Computer Assisted Language Learning (CALL) learning environments.…”
Section: Related Studiesmentioning
confidence: 99%
See 1 more Smart Citation